Computational Systems Bioinformatics 2008
DOI: 10.1142/9781848162648_0029
|View full text |Cite
|
Sign up to set email alerts
|

Graph Wavelet Alignment Kernels for Drug Virtual Screening

Abstract: In this paper we introduce a novel graph classification algorithm and demonstrate its efficacy in drug design. In our method, we use graphs to model chemical structures and apply a wavelet analysis of graphs to create features capturing graph local topology. We design a novel graph kernel function to utilize the created feature to build predictive models for chemicals. We call the new graph kernel a graph wavelet-alignment kernel.We have evaluated the efficacy of the wavelet-alignment kernel using a set of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In the previously mentioned node extraction method, we ignore the neighborhood topology information of the chemical compound by focusing on atom physical and chemical properties. To add neighborhood topology information, we utilize a technique called the graph wavelet analysis, as originally presented in [ 21 ]. The output of the wavelet analysis is a vector of local feature averages, with the size of the vector controlled by a diffusion parameter d .…”
Section: Methodsmentioning
confidence: 99%
“…In the previously mentioned node extraction method, we ignore the neighborhood topology information of the chemical compound by focusing on atom physical and chemical properties. To add neighborhood topology information, we utilize a technique called the graph wavelet analysis, as originally presented in [ 21 ]. The output of the wavelet analysis is a vector of local feature averages, with the size of the vector controlled by a diffusion parameter d .…”
Section: Methodsmentioning
confidence: 99%
“…The optimal assignment kernel [11] computes optimal assignment between two attributed molecular graphs and uses that similarity score as the value of the kernel function for classification. In [10], graph wavelet alignment kernels were proposed and experiments showed that they can achieve comparable performances like optimal assignment methods but are generally faster.…”
Section: B Graph Kernelsmentioning
confidence: 99%
“…Using graph representations of chemical structures have become popular in recent research [10] [11]. It is easy to model chemical compounds by a graph representation where nodes are usually used to model atoms in the chemical structure and edges are used to model bonds in the chemical structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crovella and Kolaczyk used graph wavelet theory to analyze the network traffic data [50]. Smalter et al applied graph wavelet theory to drug virtual screening [51].…”
Section: Introductionmentioning
confidence: 99%